Reactive oxygen species may be involved in the distinctive biological effects of different doses of 12C6+ ion beams on Arabidopsis - Yin, Yue; Cui, Dongjie; Chi, Qing; Xu, Hangbo; Guan, Panfeng; Zhang, Hanfeng; Jiao, Tao; Wang, Xiaojie; Wang, Lin; Sun, Hao (Frontiers in Plant Science, 2024)
Heavy ion beam is a novel approach for crop mutagenesis with the advantage of high energy transfer line density and low repair effect after injury. Herein, this study investigated the biological effect of heavy ion beam on Arabidopsis. The results showed that the effect of heavy ion beam on Arabidopsis growth was dose-dependent. 50 Gy irradiation significantly stimulated the growth of Arabidopsis seedlings, as indicated by an increase in root and biomass, while 200 Gy irradiation significantly inhibited the growth of seedlings, causing a visible decrease in plant growth. Monte Carlo simulations revealed that high-dose irradiation caused various damage. Evidence of reactive oxygen species (ROS) and antioxidant systems implied that the damage of phenotypes in plant cells may be associated with oxidative stress. Transcriptomic analysis of the seedlings showed that a total of 170 differentially expressed genes (DEGs) were identified both in 50 and 200 Gy groups, which were mainly associated with the stress resistance and cell wall homeostasis. Further GO enrichment analysis of DEGs unique to 50 and 200 Gy revealed that 58 50 Gy-exclusive DEGs were enriched in response to the oxidative stress and jasmonic acid (JA) terms, while 435 200 Gyexclusive DEGs were enriched in relation to the oxidative stress, organic cyclic compounds, and salicylic acid (SA). This study improves the insights into the distinctive biological effects and underlying mechanisms of different dose of heavy ion irradiation on plant cell.